Nitroglycerin‐induced changes in facial skin temperature: 'cold nose' as a predictor of headache?. (19th April 2013) - Zaproudina, Nina; Närhi, Matti; Lipponen, Jukka A.; Tarvainen, Mika P.; Karjalainen, Pasi A.; Karhu, Jari; Airaksinen, Olavi; Giniatullin, Rashid
Summary Nitroglycerin (NTG) often induces headaches when used to treat cardiac diseases. Such property of NTG has been widely used in modelling of migraine‐like headaches. However, background reasons, predisposing to the development of NTG‐headache, are less studied. The main aim of our study was to find, using NTG model, easily accessible markers of the vascular changes associated with headache. Because changes in the blood flow alter the local skin temperature (Tsk), we studied the relationship between the regional changes in the facial Tsk and NTG‐induced headaches. Tsk was measured with infrared thermography in 11 healthy women during 3 h after sublingual NTG administration. NTG caused headache in five women, and four of them were the first‐degree relatives of migraine patients. Notably, before NTG administration, subjects in the headache group had lower Tsk values, especially in the nose area, than women in the pain‐free group (n = 6). NTG‐induced headache was associated with a long‐lasting increase of Tsk over the baseline. In sharp contrast, in the pain‐free group, the Tsk reduced and returned rapidly to the baseline. Thus, the low baseline level and greater increase of regional Tsk correlated with the incidence of headache that supports a role of greater vascular changes in headache happening on the basis of the dissimilarities in vascular tone. An easily accessible phenomenon of 'cold nose' may indicate background vascular dysfunctions in individuals with predisposition to headache. Facial infrared thermography, coupled with NTG administration, suggests a novel temporally controlled approach for non‐invasive investigation of vascular processes accompanying headaches.